Use of epoxy resins with incorporation of fillers for concrete rehabilitation - Silva, Luís F. F. T. (2009)
The use of polymeric materials in civil construction makes possible original bonding processes because they have good adhesion. Among the polymeric materials, the epoxies are the most advantageous in the application for concrete rehabilitation. In this paper the bond between fresh/hardener concrete was made using epoxy resins in aqueous solution, because in previous tests they obtained the best results. This study analyzes the incorporation of one filler in the epoxy resin, to understand until what quantity we can add without significant decrease of the adhesion. A conventional hardened concrete was used. Otherwise, two types of fresh concretes were used with the purpose to understand the influence of the strength class in adhesion. The evaluation of adhesion between fresh and hardened concrete was made using two shear tests - direct and slant. The results showed that the direct shear test is better than the slant because the mixed failure make easier the study of the adhesion. The incorporation of the filler is benefic and the optimal quantity of filler seems to be related with the concrete strength class.